BUDAYA KESOPANAN PESERTA DIDIK DALAM INTERAKSI SESAMA TEMAN DI SEKOLAH DASAR - Nur Awal Nasution; Alwi Dhani (Titik Fokus Karya, 2025)
This study aims to describe students’ politeness culture in peer interactions among fifth-grade students at Elementary School Negeri 1501 Hurung Jilok and to identify the constraints encountered in its practice. The study employed a descriptive qualitative approach involving 22 fifth-grade students as research participants. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. Data credibility was ensured through source and technique triangulation. The findings indicate that students’ politeness culture in peer interactions is manifested in various forms of social behavior, including giving and receiving advice, helping peers, forgiving after conflicts, and sharing feelings with close friends. In addition, interactions characterized by teasing, mocking, the use of harsh language, and uncontrolled emotional expressions were also observed in certain situations. These findings suggest that politeness practices in peer interactions are contextual and shaped by the dynamics of peer relationships. The constraints identified in this study include differences in interpreting social behavior, limited observation time, and subjectivity in assessment. This study provides an empirical description of students politeness culture in peer interactions as part of the social dynamics within the elementary school environment.